HUBUNGAN KESADARAN GIZI KELUARGA DENGAN STATUS GIZI ANAK BAWAH DUA TAHUN (BADUTA) DI KABUPATEN PURWOREJO - Ida Nurhayati; Mohammad Hakimi; T. Ninuk Sri Hartini (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2004)
THE RELATIONSHIP BETWEEN FAMILY NUTRITION AWARENESS AND THE NUTRITIONAL STATUS OF CHILDREN UNDER TWO YEARS IN PURWOREJO DISTRICT.Background: Children under two years of age are at risk of malnutrition and should be given appropriate foods. Family Nutrition Awareness is a feeding practice provided by consumption of variety foods and balanced diet. Prevalence of malnutrition among children under two years of age were still high. This phenomenon is interested to be studied.Objectives: The study was aimed to determine the role of Family Nutrition Awareness in nutritional status among children under two years in Purworejo District. Methods: A cross-sectional study was conducted in Purworejo District. In all, nutritional status and complementary feeding for 350 children under two years of age were included in the analyses. Data were collected in 2003. Family Nutrition Awareness was the total scores of variety foods consumed, exclusive and complementary breast feeding, high-dose of vitamin A supplementation and child weighing. Nutritional status (weigth for age) was measured by using Z-score based on WHO-NCHS criteria. Data were analyzed by using Polychotomous Logistic Regression. Results: The result showed that composite index of Family Nutrition Awareness was not related with nutritional status. Only one of five Family Nutrition Awareness indicators had significant association with nutritional status, i.e. consumption of variety foods (p=0.005). Family Nutrition Awareness had more nutrition impact among children below 6 month old than that 6-23 month old. The number of family members was significantly associated with nutritional status (p<0.05), except for over-nutrition. Compared to family with less than 5 members, those with 5-7 members and over 7 members were 10 and 20 times at high risk of having severe malnutrition respectively (CI=8.59-46.71 and CI=4.47-21.34). Only 4.9% children were practicing exclusive breast feeding. Intervention should be done by Government by: 1) intensiftying Family Nutrition Awareness since the prevalence of underweight was still high; 2) keeping on the family planning program, 3) emphasizing on consumption of variety foods;  4) increasing breastfeeding promotion.Conclusion: Indicators of Family Nutrition Awareness, i.e. the consumption of variety foods had significant associantion with nutritional status considering the number of family members.